Security framework Communications of Asynchronous Transfer Mode - Saleh, Intisar K.; Beshaw, Faisal G. (International Journal of Psychosocial Rehabilitation, 2020)
There is growing enthusiasm for improving broadband communication administrations and networks for business use in both local area-wide networks. The main reasons are that demands for increased bandwidth for the interconnection of remote sites and “high speed data transmission” of mass data including photographs etc. must have to meet.The features of network traffic have also changed significantly.The form of the burst traffic is increasingly characterized by a constant requirement for multi-megabytes of bandwidth.The necessity for evolving and unclear data bandwidth transfer requirements has increased with the evolution of another era of networking technologies. The ATM system is used mainly for broadband networks communication under cellular ISDN banners. ATM provides high-speed interconnection in Mbit / s or Gbit / s across wide areas, which removes the bottleneck from networks to end frameworks.For addition, on demand, the client can access data transfer capabilities and the client is actually charged for the transmission power. As more information is transferred through ATM networks (audio, images and data), security issues get more critical. The rapidly growing usage of the Internet to transfer confidential and sensitive information only enhances the importance of security services.One could even argue that the success of ATM is not determined by its efficiency but by the degree of confidence in its performance, safety and availability. The purpose of this thesis is to address questions relating to the design of ATM network security services.